2022
DOI: 10.5194/acp-22-8951-2022
|View full text |Cite
|
Sign up to set email alerts
|

Budget of nitrous acid (HONO) at an urban site in the fall season of Guangzhou, China

Abstract: Abstract. High concentrations of nitrous acid (HONO) have been observed in the Pearl River Delta (PRD) region of China in recent years, contributing to an elevated atmospheric oxidation capacity due to the production of OH through HONO photolysis. We investigated the budget of HONO at an urban site in Guangzhou from 27 September to 9 November 2018 using data from a comprehensive atmospheric observation campaign. During this period, measured concentrations of HONO were 0.02 to 4.43 ppbv, with an average of 0.74… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 173 publications
0
5
0
Order By: Relevance
“…CC BY 4.0 License. variations of oxidation levels and other sources such as HONO photolysis (Yu et al, 2022) also 384 contribute to OH radicals and is a typical oxidant in daytime photochemistry. To investigate the 385 possible roles of aqueous reactions in SOA formation, the relationship between apparent SOA rates 386 and corresponding average ALWC were also investigated, and a positive but weak correlation was 387 found (r=0.33).…”
Section: Discussion On Soa Formation Mechanismsmentioning
confidence: 99%
“…CC BY 4.0 License. variations of oxidation levels and other sources such as HONO photolysis (Yu et al, 2022) also 384 contribute to OH radicals and is a typical oxidant in daytime photochemistry. To investigate the 385 possible roles of aqueous reactions in SOA formation, the relationship between apparent SOA rates 386 and corresponding average ALWC were also investigated, and a positive but weak correlation was 387 found (r=0.33).…”
Section: Discussion On Soa Formation Mechanismsmentioning
confidence: 99%
“…Based on the differences in the types of inorganic compounds, organic compounds (further dividing OVOCs into dialdehydes and nondialdehydes) and radicals, 15 sensitivity tests (Table 3) were designed and performed with the box model to identify the changes in RO 2 * concentrations resulting from constraining and not constraining HONO, OVOC species and NO 3 radicals. The HONO data were measured at the same site with a custom‐built long‐path absorption photometer (Yu et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Note that the method described here is specifically designed for the detection of pyrogenic HONO. Although elevated HONO concentrations are associated with anthropogenic activities (Spataro and Ianniello, 2014;VandenBoer et al, 2014;Kramer et al, 2020;Zheng et al, 2020;Yu et al, 2022;Zhang et al, 2023a), up to now no HRI enhancements have been observed with IASI in proximity to anthropogenic sources (e.g., megacities, industrial clusters).…”
Section: Hono Detection Filtermentioning
confidence: 96%
“…While routine in situ measurements at the (near) surface provide valuable insights on HONO, particularly in polluted regions (VandenBoer et al, 2014;Kramer et al, 2020;Zheng et al, 2020;Yu et al, 2022;Zhang et al, 2023a), the atmospheric distribution of HONO is still poorly represented, especially in the free troposphere (Spataro and Ianniello, 2014), notably due to its high reactivity. For instance, HONO observations in biomass burning events were usually limited to local measurements from aircraft and ground-based campaigns (Yokelson et al, 2009;Roberts et al, 2010;Neuman et al, 2016;Peng et al, 2020Peng et al, , 2022Bourgeois et al, 2022).…”
Section: Introductionmentioning
confidence: 99%